Autonomous DevOps Infrastructure: AI-Driven Lifecycle Management of Large Scale Linux Server Ecosystems - Vinay Kumar Reddy Vangoor (Journal of Management and Science, 2022)
Managing large-scale Linux environments demands a shift from reactive operations to intelligent, proactive systems. As infrastructure grows into the thousands of nodes, human-driven workflows become inefficient, error-prone, and costly. This is where autonomous DevOps infrastructure emerges as a transformative solution, leveraging artificial intelligence to continuously monitor, analyze, and optimize system behavior without constant human intervention. In this architecture, machine learning models play a critical role by analyzing historical  and real-time telemetry data to predict potential failures before they occur. This predictive capability allows the system to take preventive actions, significantly reducing unplanned downtime. Reinforcement learning agents further enhance autonomy by dynamically learning optimal responses to configuration drifts, performance bottlenecks, and system anomalies, improving decision-making over time. Additionally, large language models contribute by automatically generating context-aware remediation scripts and operational runbooks. This eliminates the need for manual documentation and accelerates incident resolution. The integration of these AI components creates a closed-loop system capable of detecting, diagnosing, and resolving issues in real time. The real-world deployment across 3,200 Linux servers demonstrates the system’s effectiveness. A dramatic reduction in mean time to repair, improved SLA compliance, and a high percentage of self-resolved incidents highlight its operational impact. Beyond performance improvements, the significant cost reduction underscores the economic value of automation. Ultimately, autonomous DevOps represents the future of infrastructure management scalable, resilient, and intelligent systems that redefine efficiency in enterprise IT operations.